Effect of casein phosphopeptide amorphous calcium fluoride phosphate and calcium glycerophosphate on incisors with molar-incisor hypomineralization: A cross-over, randomized clinical trial - TUĞCU, NİHAN; DURMUŞ, BAŞAK; KARGÜL, BETÜL; BEKİROĞLU, GÜLNAZ NURAL (My University, 2022)
BACKGROUND:Within the scope of minimally invasive dentistry, the use of different biocompatible remineralization agents on incisors affected by molar-incisor hypomineralization (MIH) gains importance. OBJECTIVE:To evaluate the effect of casein phosphopeptide amorphous calcium fluoride phosphate (CPP-ACFP) and calcium glycerophosphate (CaGP) in mineral density (MD) of white/creamy and yellow/brown demarcated opacities on incisors affected by MIH by means laser fluorescence (LF). METHODS:As a cross-over, randomized trial, twenty-two children with 167 incisors affected by MIH were recruited and randomly assigned to one of the two different agents and crossed over to other agents with two weeks washout in between. Incisors were examined by using LF at all before and after three months periods. RESULTS:The results of the paired t-tests for determining the period effect between the baseline findings showed significant difference in white/creamy and yellow/brown demarcated opacities of LF values for both groups (p < 0.05). The difference between both groups according to after categorization of 20% increasing in MD in the percent of change before and after application on LF values; was not found statistically significant in white/creamy (p = 0.970) and yellow/brown (p = 0.948) opacities. CONCLUSIONS:The primary outcome was CPP-ACFP and CaGP had a positive effect in decreasing hypomineralization on MIH-affected enamel for three months period. Keywords: Molar incisor hypomineralization, minimally invasive dentistry, remineralization, preventive dentistry, casein phosphopeptide amorphous calcium fluoride phosphate, calcium glycerophosphate
Keywords: Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Biomedical Engineering; Engineering and Technology; MÜHENDİSLİK, BİYOMEDİKAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, BİYOMATERYAL; Malzeme Bilimi; ENGINEERING, BIOMEDICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE; Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Genel Mühendislik; Biyomedikal mühendisliği; Mühendislik (çeşitli); Biyomühendislik; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); General Materials Science; General Engineering; Engineering (miscellaneous); Bioengineering; Physical Sciences; Molar incisor hypomineralization; minimally invasive dentistry; remineralization; preventive dentistry; casein phosphopeptide amorphous calcium fluoride phosphate; calcium glycerophosphate; DEMINERALIZATION; TEETH; MIH